Wicked ways - Keene, Carolyn; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 1996)
Nancy tracks down a shoplifter who is stealing designer jackets from a store in the mall.
"An Archway paperback."
Keywords: Shoplifting -- Fiction; Shoplifting -- Juvenile fiction; Drew, Nancy (Fictitious character) -- Juvenile fiction; Shoplifting -- United States -- Juvenile fiction; Fashion shows -- United States -- Juvenile fiction; Young adult fiction; Mystery fiction